Utilization of Aloe Vera as Herbal Medicine in Sobawagoli Village - Karunia Gea; Murnihati Sarumaha; Hilaria Santi Kristiani Harefa (Jurnal Riset Rumpun Ilmu Tanaman, 2026)
This study examines the utilization of Aloe vera as a herbal medicine by the community of Sobawagoli Village, Indonesia. The research aims to document local knowledge related to the processing, application, and perceived benefits of Aloe vera in traditional healthcare practices. A qualitative descriptive approach with a case study design was employed. Data were collected through direct field observations, in-depth interviews with community members, and documentation of preparation methods. The findings reveal that Aloe vera is widely used for both internal and external treatments, including digestive disorders, internal heat, hypertension, burns, skin inflammation, and natural skin and hair care. The plant is processed through simple methods such as boiling, blending, and direct topical application, reflecting the accessibility and practicality of herbal medicine in rural settings. Community perceptions toward Aloe vera are highly positive, viewing it as a safe, effective, and culturally embedded alternative to chemical medicines. These practices are supported by empirical experiences and align with recent scientific studies highlighting the therapeutic properties of Aloe vera. The study underscores the importance of preserving indigenous herbal knowledge and integrating it with modern health education to promote sustainable, community-based healthcare systems.